PENGGUNAAN REDESAIN BANTAL MENYUSUI MENINGKATKAN MOTIVASI IBU MENYUSUI DAN KEPUASAN BAYI SERTA MENGURANGI KELELAHAN DAN KELUHAN MUSKULOSKELETAL IBU POST PARTUM - Muliarthini, Ni Wayan; Sutjana, I Dewa Putu; Adiatmika, I Putu Gede (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2016)
Breastfeeding is a very important activity for both mother and baby. In the breastfeeding state the relationship between mother and baby will be tight and close. The old method and also duration of breastfeeding can cause fatigue, shoulder muscle tension, and soreness / stiffness in breastfeeding mothers. Problems due to absence of the use of pillow when mother breastfeed and mothers only depending on her limb to sustain baby when breastfeeding. In this case we need an ergonomic pillow to help mother feeding her baby. The purpose of this research is to investigate the use of redesigning nursing pillow can reduce fatigue, musculoskeletal complaints in breastfeeding mothers, to determine the use redesigning nursing pillow increase the motivation of mothers to breastfeed the baby as well as increase the satisfaction of nursing infants.This research held in as an experimental research draft of pre and post control group design. Samples that were included in this study was 22 people divided into two groups. The control group will breastfeeding using older model nursing pillow, while the another group will use the new redesign nursing pillow. Data analysis using t-test paried significance level of 5%.The result showed mother’s motivation after breastfeeding in both groups increased, the control group (18.27 ± 2.370) and the treatment group (15.45 ± 1.809). Baby satisfaction in the control group (11.09 ± 0.943), while the treatment group (12.27 ± 0.904). Exhausted mother’s in the control group (39.64 ± 2.803), while the treatment group (32.64 ± 1.504).Musculoskeletal disorders that mother’s felt in the control group (37.54 ± 1.694), while the treatment group (30.81 ± 2.136).Based on the study can be concluded that redesign breastfeeding pillow can giving impact to increase motivation and baby satisfaction and also decrease fatigue and musculoskeletal complain/disorder that mothers can feel. So hopefully by using this nursing pillow design maximizes mothers to breastfeed
Keywords: Redesign Pillow, Motivation, Baby Satisfaction, Fatigue And Musculoskeletal Complaints